All-star - Linda Lee (McGraw-Hill ESL/ELT, 2005)
All-Star is a four-level, standards-based series for adult English learners featuring a picture-dictionary approach to vocabulary building. Big picture scenes in each unit provide springboards to a wealth of activities that develop all the language skills. An accessible, step-by-step sequence of lessons in each unit systemically builds language and math skills around life-skill topics. The series presents a family, work, or community application in each unit, and provides two alternate lesson applications in each of the All Star Workbooks